Discovery of Yaozhuang Stock and Deep Ore Prospecting Implication for the Western Mangling Orefield in North Qinling Terrane, Central China - Fan, Peng; Xi, Aihua; Zhou, Bin; Chao, Xu; Yang, Wenbo; Sun, Jiaxin; Zhu, Hongyu; Wei, Li (Frontiers in Earth Science, 2022)
In the western Mangling orefield, the molybdenum (Mo) polymetallic deposits are closely related to the ore-bearing porphyry stocks (individual outcrop size: < 1 km2). In this study, we have discovered several granitic stocks at Yaozhuang. Systematic petrologic, zircon U-Pb-Hf isotope and whole-rock geochemical studies show that both the granitic stocks of porphyritic granite (157 ± 2 Ma) and the intruding monzogranite dyke (153 ± 1 Ma) emplaced in the Late Jurassic. These granitic stocks are characterized by high SiO2 (66.83−75.63 wt.%), high K2O (4.15−5.05 wt.%), high Al2O3 (12.90−16.93 wt.%) and low MgO (0.06−0.73 wt.%), and are metaluminous to weakly peraluminous, being highly-fractionated I-A type transition granites. The content of the total rare earth element (ΣREE) of the porphyritic granite (139.6−161.7 ppm) is lower than that of the monzogranite (151.4−253.6 ppm). The porphyritic granite has weakly negative Eu anomalies (Eu/Eu* = 0.77−0.93), whereas the monzogranite has weakly positive Eu anomalies (Eu/Eu* = 0.97−1.21), and are light rare earth elements (LREEs) more enriched. Both of them are enriched in large ion lithophile elements (LILEs, e.g., K, Rb and Ba), but depleted in high-field strength elements (HFSEs, e.g., Nb, Ta, Ti, Zr and Hf). The zircon εHf(t) values of all the samples range from -16.1 to -6.9, and the two-stage model ages (tDM2) are 1.78−2.16 Ga. The magma may have originated from partial melting of the lower crust (more than 40km in depth) caused by mantle-derived magma underwelling. The plutons and stocks were emplaced into the intersection of the early EW-trending faults and the late (Yanshanian) NE-trending faults. The fertile magma with high water content (H2O > 4%) and high oxygen fugacity (Delta FMQ ＞ 1.5) indicates that the Yaozhuang area has significant potential for porphyry Mo polymetallic ore discovery.